Pregnancy with COVID-19: feto-maternal outcome from a tertiary care hospital, Bangladesh - Chowdhury, Shahanara; Rashid, Fahmida; Shikha, Jahanara; Chowdhury, Samira Amir; Ahmed, Farid Uddin; Sattar, Mohammad Abdus (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The objective was to determine the maternal and fetal outcomes of pregnant women with COVID-19 infection in the southeast part of Bangladesh. Methods: A prospective observational study was conducted at Chittagong Medical College Hospital (CMCH), Bangladesh, for one year. Pregnant women were divided into suspected and confirmed groups based on the clinical features of COVID-19 and the results of RT-PCR (SARS-CoV2). Outcome measures were maternal death, ICU admission, mechanical ventilation, and stillbirth/neonatal death. The Mann-Whitney U test was applied for between-group comparisons. Binary logistic regression analysis was done for factors affecting feto-maternal outcomes. Results were presented as odds ratios (OR) and 95% confidence intervals (CI). Results: A total of 144 pregnant women (n=144) were included in the study, divided into confirmed (n=71) and suspected (n=73). Complications were more in the confirmed group (p=0.315). Caesarean section was 69% and 64.4% in the confirmed and suspected groups, respectively (p=0.556). Eight women (5.55%) needed ICU admission, five (3.5%) required mechanical ventilation, and five (3.5%) women expired. Fetal distress was seen in 15 (10.41%) pregnancies. Stillbirth or neonatal death and the need for NICU admission were higher for suspected than in confirmed cases. Pregnancies with suspected COVID-19 had 3.91 times (OR: 3.913, 95% CI: 1.398-10.954) higher poor feto-maternal outcome. Unbooked status, COVID-19 test negativity, and use of antivirals were associated with poor feto-maternal outcomes. Conclusions: Pregnancies with COVID-19 were prone to poor feto-maternal outcomes. The study pointed to an improvement in the ANC of pregnant women with COVID-19 in a public hospital like Bangladesh.